Constraint-induced aphasia therapy for patients with aphasia: A systematic review - Guandong Wang; Li Ge; Qingxiang Zheng; Pingping Huang; Jing Xiang (Elsevier, 2020)
Objectives: This study aimed to systematically evaluate the effects of constraint-induced aphasia therapy (CIAT) for aphasic patients reported by randomized controlled trials. Methods: Relevant randomized controlled trials were retrieved from 11 electronic databases. A methodological quality assessment was conducted in accordance with the Cochrane Handbook, and meta-analyses were performed by using RevMan 5.2. A descriptive analysis was conducted when the included trials were not suitable for a meta-analysis. Results: A total of 12 trials were included. A statistically significant group difference was shown from the meta-analysis in the results measured by the Western Aphasia Battery (random-effects model, MD = 1.23, 95% CI = 0.31 to 2.14, P < 0.01). However, there were no statistically significant differences shown in the results of the Boston Naming Test (fixed-effects model, MD = −1.79, 95% CI = −11.19 to 7.62, P > 0.05) and Aachen Aphasia Test (fixed-effects model, MD = −1.11, 95% CI = −4.49 to 2.27, P > 0.05). The descriptive analysis showed positive results in language performances of naming, repetition, and comprehension. Conclusion: This systematic review indicated that CIAT was efficient for improving language performance with regard to naming, comprehension, repetition, written language, and oral language based on the current evidence. And this review provides some meaningful guides for clinical practice: expand the therapy duration to 2 or 3 h per day, focus on naming, and choose the best assessment tool. It also indicates a need for more rigorous, large-scale, and high-quality trials in the future.